Pendampingan Membaca Surah Al Kahfi pada Setiap Hari Jumat Dalam Meningkatkan Nilai Spiritualitas Siswa di MA Darul Ulum Palangka Raya - Nurlisa Nurlisa; Noorazmah Hidayati; Mila Nur’aini (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Community service activities at MA Darul Ulum Palangka Raya aim to increase the spiritual value of students. Through the Asset Based Community-driven Development (ABCD) approach, the service team encourages students to regularly read Surah Al Kahfi every Friday before learning activities. Even though students already have these good habits, this potential needs to be monitored and developed. The activity took place from July to October 2024, and aimed to form positive attitudes and behaviors of students.